1992
DOI: 10.1111/j.1532-5415.1992.tb02136.x
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Cholecystokinin Secretion in Elderly with Protein‐Energy Undernutrition

Abstract: The increase of postprandial maximal levels of cholecystokinin is more related to malnutrition than to aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Masclee et al (20) found higher CCK concentrations in older than in younger subjects after intraduodenal fat infusion, but no significant difference in fasting CCK concentrations between the 2 age groups. Berthelemy et al (21) reported no significant difference in CCK concentrations, either in a fasting state or after a liquid meal, between well-nourished younger and older people, but did report that postprandial CCK concentrations were higher in malnourished older subjects than in well-nourished young and well-nourished older subjects. This is consistent with evidence that suboptimal energy intake, reduced body weight, or both may be associated with increased plasma CCK concentrations (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masclee et al (20) found higher CCK concentrations in older than in younger subjects after intraduodenal fat infusion, but no significant difference in fasting CCK concentrations between the 2 age groups. Berthelemy et al (21) reported no significant difference in CCK concentrations, either in a fasting state or after a liquid meal, between well-nourished younger and older people, but did report that postprandial CCK concentrations were higher in malnourished older subjects than in well-nourished young and well-nourished older subjects. This is consistent with evidence that suboptimal energy intake, reduced body weight, or both may be associated with increased plasma CCK concentrations (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed this by measuring plasma CCK, GLP-1, and PYY concentrations in response to intraduodenal lipid and glucose infusions and correlated these results with measures of appetite, food intake, and pyloric motility reported in a previous study (15). We were particularly interested in assessing the CCK response to intraduodenal lipid infusions because lipid is a more potent stimulator of endogenous CCK release than glucose (19) and there are conflicting reports about the effect of age on increases in plasma CCK concentrations produced by ingestion of lipid (20) or a mixed meal (21). We hypothesized that aging enhances the lipidinduced increase in CCK concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible factor is the increased postprandial cholecystokinin hormone in malnutrition based on the work of Berthelemy et al (1992). This hormone inhibits the proximal gastric contraction and hence adds to the delayed GET in PEM (Lieverse et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that CCK concentrations are higher in undernourished elderly subjects compared with the healthy elderly (345). Although circulating ghrelin concentrations increase between early adulthood and middle age in humans, there is evidence that old age is associated with decreased ghrelin concentrations in rodents and in humans (311, 346).…”
Section: Aging and Metabolismmentioning
confidence: 99%